"Laicidade" in Brazil as a booster to religious freedom. - DOI 10.5935/2448-0517.20190061 - Perlingeiro, Ricardo; Oliveira, Amanda (Juris Poiesis - Qualis A3, 2020)
This text is a starting point for the construction of a research project on religious freedom comparing legal systems of countries with an official religion, such as the United Kingdom, Costa Rica and Israel, and countries without one, such as Brazil, the USA and France. Considering the premise that a country should strive for effective human rights, the study begins an analysis of the scope of the duty of a country with no official religion to ensure religious freedom (positive and negative liberties). For this purpose, the authors make use of the Brazilian experience, with its "laicity". There is a difficulty in translating the expression "laicidade", due to language barrier and special connotations in Brazilian constitutional law. Therefore, the authors describe its three main characteristics (autonomy, cooperation and religious freedom) drawn from a recent Brazilian Supreme Court precedent. What is unique about the concept of "laicidade" is that it allows a secular state to cooperate with religious faiths, regardless of the prohibition of having an official one. This insight paves the way for future dialogues with other countries, including nations that, despite having their own official religion, are capable of working together in harmony with other religious faiths to garantee the effectiveness of their human right.